Alterations in 3-Hydroxyisobutyrate and FGF21 Metabolism Are Associated With Protein Ingestion–Induced Insulin Resistance - Harris, Lydia-Ann L.S. (Diabetes, 2017)
Systemic hyperaminoacidemia, induced by either intravenous amino acid infusion or protein ingestion, reduces insulin-stimulated glucose disposal. Studies of mice suggest that the valine metabolite 3-hydroxyisobutyrate (3-HIB), fibroblast growth factor 21 (FGF21), adiponectin, and nonesterified fatty acids (NEFAs) may be involved in amino acid–mediated insulin resistance. We therefore measured in 30 women the rate of glucose disposal, and plasma 3-HIB, FGF21, adiponectin, and NEFA concentrations, under basal conditions and during a hyperinsulinemic-euglycemic clamp procedure (HECP), with and without concomitant ingestion of protein (n = 15) or an amount of leucine that matched the amount of protein (n = 15). We found that during the HECP without protein or leucine ingestion, the grand mean ± SEM plasma 3-HIB concentration decreased (from 35 ± 2 to 14 ± 1 µmol/L) and the grand median [quartiles] FGF21 concentration increased (from 178 [116, 217] to 509 [340, 648] pg/mL). Ingestion of protein, but not leucine, decreased insulin-stimulated glucose disposal (P < 0.05) and prevented both the HECP-mediated decrease in 3-HIB and increase in FGF21 concentration in plasma. Neither protein nor leucine ingestion altered plasma adiponectin or NEFA concentrations. These findings suggest that 3-HIB and FGF21 might be involved in protein-mediated insulin resistance in humans.